Gas-induced selective re-orientation of Au–Cu nanoparticles on TiO2 (110). Issue 2 (19th December 2018) - Wilson, Axel; Bailly, Aude; Bernard, Romain; Borensztein, Yves; Coati, Alessandro; Croset, Bernard; Cruguel, Hervé; Naitabdi, Ahmed; Silly, Mathieu; Saint-Lager, Marie-Claire; Vlad, Alina; Witkowski, Nadine; et al.
Abstract : Au–Cu bimetallic nanoparticles (NPs) grown on TiO2 (110) have been followed in situ using grazing incidence X-ray diffraction and X-ray photoemission spectroscopy from their synthesis to their exposure to a CO/O2 mixture at low pressure ( P < 10 −5 mbar) and at different temperatures (300 K–470 K). Abstract : Au–Cu bimetallic nanoparticles (NPs) grown on TiO2 (110) have been followed in situ using grazing incidence X-ray diffraction and X-ray photoemission spectroscopy from their synthesis to their exposure to a CO/O2 mixture at low pressure ( P < 10 −5 mbar) and at different temperatures (300 K–470 K). As-prepared samples are composed of two types of alloyed NPs: randomly oriented and epitaxial NPs. Whereas the introduction of CO has no effect on the structure of the NPs, an O2 introduction triggers a Cu surface segregation phenomenon resulting in the formation of a Cu2 O shell reducible by annealing the sample over 430 K. A selective re-orientation of the nanoparticles, induced by the exposure to a CO/O2 mixture, is observed where the randomly oriented NPs take advantage of the mobility induced by the Cu segregation to re-orient their Au-rich core relatively to the TiO2 (110) substrate following specifically the orientation ((111)NPs //(110)TiO2 ) when others epitaxial relationships were observed on the as-prepared sample.